Elementary statistics. - Weiss, Neil A., ....- (San Francisco : Pearson, 2008)
Elementary Statistics, Seventh Edition, features a thorough presentation of the reasoning behind statistics, balanced with analysis and exploration of real data. This text emphasizes the development of statistical thinking rather than rote drill and practice. This new edition continues the author's tradition of cutting-edge statistical pedagogy and seamless integration of technology, and includes hundreds of new exercises with carefully cited data from journals, magazines, newspapers, and Web sites. Elementary Statistics, Seventh Edition, is the ideal text for instructors who teach a one-semester course and prefer a briefer presentation of topics.
Keywords: Statistiek